Indonesian Government Role in Standardizing Guidance Counseling Assessments: A Global Comparative Study - Daharnis; Zadrian Ardi; Wahidah, Syarifah (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This study aims to examine the role of Indonesian government in standardizing guidance and counseling assessment through comparative policy analysis among several countries and draw multiple implications for strengthening the assessment system in Indonesia. Professional guidance and counseling services require standardized assessments to objectively identify student needs, design appropriate interventions, and evaluate the effectiveness of services. This research applied a qualitative descriptive-comparative approach with data collection techniques through document analysis of policy papers and expert interviews. The data were thematically and comparatively analyzed across countries. The results reveal that countries such as Finland, South Korea, and the United States have engaged powerful policy frameworks for guidance counseling assessment, including national regulations, standardized instruments, evaluation and supervision systems, and the integration of assessment into the educational system. However, national standard has not yet to be established in Indonesia consisting of the terms of instruments, procedures, and reporting systems. The findings indicate that the government should actively get involved in developing technical policies for the counseling assessment, enhancing the professional counselor’s capacity, and formulating data-based supervision systems. This research conceptually contributes to the development of counseling assessment policies and encourages the integration of assessment as a part of data-based education system.